Stress Analysis in Glass Artwork - João M. P. Coelho; Catarina Silva; Teresa Almeida (International Journal of Optics)
A simple method for determining the stress fields in transparent glass artwork pieces is presented. The proposed method is based on the principles of photoelasticity combining imaging and quantitative measures with an image processing algorithm. The main goal was to develop a methodology to help glass artists to determine the ability of their work to resist the thermal shocks by giving them a hazard map based on the stress map of the glass piece.